STAT1 is required to establish but not maintain interferon‐γ‐induced transcriptional memory - Tehrani, SS; Mikulski, P; Abdul‐Zani, I; Mata, JF; Siwek, W; Jansen, LE (EMBO Press, 2023)
Exposure of human cells to interferon‐γ (IFNγ) results in a mitotically heritable yet reversible state called long‐term transcriptional memory. We previously identified the clustered GBP genes as strongly primed by IFNγ. Here, we discovered that in primed cells, both interferon‐responsive transcription factors STAT1 and IRF1 target chromatin with accelerated kinetics upon re‐exposure to IFNγ, specifically at promotors of primed genes. Priming does not alter the degree of IFNγ‐induced STAT1 activation or nuclear import, indicating that memory does not alter upstream JAK–STAT signaling. We found STAT1 to be critical to establish transcriptional memory but in a manner that is independent of mere transcription activation. Interestingly, while Serine 727 phosphorylation of STAT1 was maintained during the primed state, STAT1 is not required for the heritability of GBP gene memory. Our results suggest that the memory of interferon exposure constitutes a STAT1‐mediated, heritable state that is established during priming. This renders GBP genes poised for subsequent STAT1 and IRF1 binding and accelerated gene activation upon a secondary interferon exposure.